Real-World Cost-Consequence Analysis of an Integrated Chronic Disease Management Program in Saskatchewan, Canada - John Paul Kuwornu; Fernando Maldonado; Gary Groot; Erika Penz; Elizabeth J Cooper; Amy Reid; Darcy D Marciniuk (SAGE Publishing, 2024)
An integrated disease management program otherwise called a clinical pathway was recently implemented in Saskatchewan, Canada for patients living with chronic obstructive pulmonary disease (COPD). This study compared the real-world costs and consequences of the COPD clinical pathway program with 2 control treatment programs. The study comprised adult COPD patients in Regina (clinical pathway group, N = 759) matched on propensity scores to 2 independent control groups of similar adults in (1) Regina (historical controls, N = 759) and (2) Saskatoon (contemporaneous controls, N = 759). The study measures included patient-level healthcare costs and acute COPD exacerbation outcomes, both tracked in population-based administrative health data over a one-year follow-up period. Analyses included Cox proportional hazards models and differences in means between groups. The bias-corrected and accelerated bootstrap method was used to calculate 95% confidence intervals (CI). The COPD pathway patients had lower risks of moderate (hazard ratio [HR] =0.57, 95% CI [0.40-0.83]) and severe (HR = 0.43, 95% CI [0.28-0.66]) exacerbations compared to the historical control group, but similar risks compared with the contemporaneous control group. The COPD pathway patients experienced fewer episodes of exacerbations compared with the historical control group (mean difference = −0.30, 95% CI [−0.40, −0.20]) and the contemporaneous control group (mean difference = −0.12, 95% CI [−0.20, −0.03]). Average annual healthcare costs in Canadian dollars were marginally higher among patients in the COPD clinical pathway (mean = $10 549, standard deviation [SD] =$18 149) than those in the contemporaneous control group ($8841, SD = $17 120), but comparable to the historical control group ($10 677, SD = $21 201). The COPD pathway provides better outcomes at about the same costs when compared to the historical controls, but only slightly better outcomes and at a marginally higher cost when compared to the contemporaneous controls.